If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1x = 2y Solving 2 + -1x = 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = -2 + 2y Combine like terms: 2 + -2 = 0 0 + -1x = -2 + 2y -1x = -2 + 2y Divide each side by '-1'. x = 2 + -2y Simplifying x = 2 + -2y
| 2(5v+3)-4(7v+1)=-88 | | 40(6x-3y)=105 | | 3(4x-2)=6(-2x-3) | | 25+0.25p= | | 6n=2n+16 | | 8=-18+0.375(16-40n) | | -16.5-4.5+6=-15 | | 2(n+3)=6+4(n+8) | | 77+20x=400 | | (5x-7.66666667)-(-7x+4.25)= | | -x+61=218 | | -F-4.5+6=-15 | | 6c-13-43=-49 | | 1250•5/7=x | | -0.3(9x+42)-5x=-70 | | -3x-3x+3y=3 | | (y+0)=6(x-4) | | 5/3g-1/3=-10/3 | | 275-u=80 | | -5g+-2.3=-18.8 | | 20f-6=2 | | 6000/4800 | | 65+12t=0 | | x+(x-34)=180 | | 50y=5-x | | 5x+4x+3=48 | | 5-(y+3)=-1+2(t-3) | | 12x+6=3x+36 | | 29×2/7 | | 1250=5/7x | | -1+(-4d)=-15 | | 7(a+x-b)-8(a-x-b)=-(b-x) |